The Role of Aeolin in The Formation of Earth Surface Configuration and The Influencing Factor - Anna, Alif Noor (Forum Geografi, 1997)
Configuration of the earth surface is molded by the interaction of endogenous and exogenous forces. The outcome of the interaction usually has the shape of special charracter. Configuration charracter is then applied to grouping of more simple form called landform. It so happens that one of the landform function is to make geomorphology research more easier. Que of the earth surface configuration is molded by wind force the result of this activity is called the landform which is originally molded by wind process. There are two folds function of wind process i.l: erosion (= coracoid process and deposifronal force). Coracoid process usually takes place on vertical as well as horizontal plane. Coracoid on vertical plane will have the shape of yardang, while on horizontal plane has the shape of pillars, needless, and zenguen. It so happens that depositional wind will shape ripples, sanddunes, and loess.